A new approach to achieve a fast acting MPPT technique for solar photovoltaic system under fast varying solar radiation - Vijay Muni, T; V N L Lalitha, S; Krishna Suma, B; Venkateswaramma, B (International Journal of Engineering and Technology, 2018)
In this paper, a new control technique is proposed to achieve a fast acting Maximum Power Point Tracking (MPPT) Technique for solar photovoltaic system under fast varying solar radiation. Conventional MPPT techniques in PV systems fail to track maximum power point (MPP) under fast varying of sunlight levels. In the proposed MPPT algorithm a fine tuned duty cycle for a DC-DC converter is achieved to avoid the divergence of MPP. This can be achieved from the relationship between the load line and the MPP locus. The MPPT algorithm is used to regulate the duty cycle of a DC-DC converter to ensure that always the load line cuts the I-V curve at MPP. The effectiveness of the proposed PV-MPPT system is demonstrated via case studies and simulation results shows the effective performance of the fast acting MPPT technique in achieving efficient MPP.Â Â